The Effectiveness of The Media Leaflets and Film on Knowledge of The Attitude snd Skills of Cadres in Ovitrap Making - Fitri Saragih; R. Kintoko Rochadi; Alam Bakti Keloko (International Archives of Medical Sciences and Public Health, 2021)
Introduction: Ovitrape is one method for preventing the occurrenceof DHF. Ovitrape has been widely used in a variety of locations witha high prevalence of DHF. One of the advantages of ovitrape is that itis simple to manufacture and inexpensive. The purpose of this studyis to determine the effectiveness of video media in increasingknowledge and skills in making ovitrape. Method: This is a quasiexperimental design with a pretest-posttest format. This researchsample included 50 cadre divided into two groups, 25 groups, and 25media leaflet film media. The Wilcoxon and Mann Whitney tests areused in this study. Result : Wilcoxon test results indicated leafletsand film media effectively improve cadres' knowledge, attitude, andskills in ovitrape manufacture. The film is a more effective mediumfor improving cadres' knowledge, attitudes, and skills in themanufacture of ovitrape. Conlusion According to the researchfindings, the collaboration between the health centre and PanguluNagori Batu Anam Pamatang Simelungun District of SiantarSimalungun is necessary for inserting health education materialsabout dengue prevention through the use of film and leaflets.